Inter-observer variation in gross tumour volume delineation of oesophageal cancer on MR, CT and PET/CT - Secerov-Ermenc Ajra; Peterlin Primoz; Anderluh Franc; But-Hadzic Jasna; Jeromen-Peressutti Ana; Velenik Vaneja; Segedin Barbara (Radiology and Oncology)
The aim of our study was to assess the inter-observer variability in delineation of the gross tumour volume (GTV) of oesophageal cancer on magnetic resonance (MR) in comparison to computed tomography (CT) and positron emission tomography and CT (PET/CT).